MERDEKA MENGAJAR PLATFORM IN ELT OF MPLEMENTING KURIKULUM MERDEKA AT SMKN 1 TORAJA UTARA: CHALLENGES AND OPPORTUNITIES - Two Indah Tangaran, Glory; Tulaktondok, Linerda (Publikasi dan UKI Press UKI Toraja., 2024)
The aim of this research is to find out what the challenges and opportunities are for English teachers using the Merdeka Mengajar Platform. The background of this research is that, as a new platform, the Merdeka Mengajar Platform requires quick adaptation from teachers, but the problem is that currently in the Merdeka Mengajar Platform there are still many teachers who are confused about implementing the Merdeka Mengajar Platform. In this research, the researcher used a qualitative approach and collected data through interviews and observation. Interview data was obtained from 3 English teachers. The results of this research are based on the findings that the use of the Merdeka Mengajar Platform really helps English teachers in creating creative modules and teaching methods in teaching English, becoming content creators or English tutors because in PMM there are lots of inspirational videos, increase teacher competency and have more freedom in teaching students based on their needs and interests. Apart from that, there are also opportunities in using PMM, there are also challenges such as technical challenges no training routine, time management, and unstable internet connection, the teaching module in PMM is not yet available so that the completeness and implementation of PMM features is still low. In the research, it was also found several ways English teachers overcome challenges and how they maximize opportunities in using PMM.